PSX-36 Late-Breaking Abstract: Effect of increasing levels of soy hulls in finishing diets of feedlot cattle offered free-choice hay on performance, roughage intake and carcass characteristics. (30th November 2020) - Pittaluga, Alejandro; Felix, Tara L; Relling, Alejandro E
Abstract: The objective of this study was to evaluate the effect of increasing quantity of soy-hulls in diets of feedlot cattle offered free-choice hay on finishing performance, roughage intake, and carcass characteristics. Sixty heifers and 54 steers, Angus*Simangus-crossbreds, were used in a randomized complete block design. Cattle were stratified by sex and weight and randomly assigned to 1 of 12 pens. Treatment 1 consisted of 5% soy hulls (SH; 5%SH), 70% cracked corn (CC), 15% dry distiller grains with soluble (DDGS), 10% mineral supplement (SUP). Treatments 2 (10%SH) and 3 (15%SH) included an additional 5% and 10% SH in place of CC, respectively. Hay was offered ad libitum and separate from the concentrates in different bunks, both concentrate and forage were fed in GrowSafe units. Data were analyzed as a complete block design and mean differences in group means were determined using polynomial contrast [lineal (L) and quadratic (Q)]. There was a quadratic effect of soy hull inclusion on final body weight (fBW) and concentrate intake (Q-P ˂ 0.05); 5%SH and 15%SH had a greater fBW and concentrate intake compared to those fed 10%SH. Gain to feed ratio was not affected by treatments (L-P ≥ 0.33). There was a linear effect of SH on hay intake (L-P ˂ 0.05) with cattle fed 5%SH consuming less hay than those fed 15%SH. There was no effect on ribeye area, yield grade, or backfat (L-P ≥ 0.35; Q-P ≥ 0.14). Hot carcass weight tended to quadratically respond to dietary treatments (Q-P < 0.10), while marbling score tended to be linearly decreased by increased SH inclusion (L-P = 0.09). Kidney-pelvic-heart fat was linearly decreased by increased SH inclusion (L-P ˂ 0.05). Results indicate that non-roughage NDF from by-products can effectively contribute to a reduction of roughage utilization in feedlot diets without compromising growth performance or carcass characteristics.